ANALISIS TEBAL PERKERASAN LENTUR METODE MDP 2017 DENGAN SOFTWARE KENPAVE - Rizal, Rikki Sofyan; Prihutomo, Nuzul Barkah; Yelvi, Yelvi (Construction and Material Journal, 2025)
The existence of the Bawen-Salatiga toll road has caused an increase in the volume of vehicles on the Tingkir Road section, Salatiga City. In the first year of the opening of the toll gate, the maximum volume of vehicles per day was 23,937, while in the second year there were 26,203 vehicles passing through per day. This number continues to experience a significant increase over time. In order to reduce the potential for traffic congestion, PT Trans Marga Central Java plans to widen the road section. This study aims to determine the thickness of the pavement and the cost that will be used in the Jalan Tingkir widening project, Salatiga City. The pavement thickness calculation employs the 2017 road pavement design manual method (MDP) and utilizes Kenpave software for structural analysis. The second edition of the Central Java Province Construction Work Unit Price (HSP) for clan buildings is used as a reference for determining the cost of pavement work. Based on the results of the analysis, the thickness of the pavement layer was obtained: 40 cm for the AC-WC layer, 60 cm for the AC-BC layer, 80 cm for the AC base layer, and 30 cm for the class A foundation layer with a planned traffic load of 3.85 x 10⁶. ESAL. As for the strength value tested with Kenpave software, the repetition value of fatigue crack load (Nf) was 3.70 x 1012, the repetition value of groove crack load (Nd) was 4.41 x 106, and the repetition value of permanent deformation load was 3.19 x 1011. Based on the analysis of the cost budget plan, the cost for the pavement work was Rp9,019,773,857.81. The flexible pavement with a thickness of 48 cm can withstand the weight of fatigue cracking, groove cracking, and permanent deformation.